2005
DOI: 10.1042/bj20050517
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular colocalization and interaction of IGF-binding protein-2 with the cyclin-dependent kinase inhibitor p21CIP1/WAF1 during growth inhibition

Abstract: It is presently unknown whether any member of the IGFBP (insulin-like growth factor binding protein) family directly participates in the control of cell proliferation. We have previously documented that induction of IGFBP-2 was associated with inhibition of DNA synthesis in lung alveolar epithelial cells. In the present study, we investigated the relationship between IGFBP-2 and the cell cycle inhibitor p21CIP1/WAF1 further. We used serum deprivation to inhibit the proliferation of MLE (mouse lung epithelial)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 41 publications
(47 reference statements)
1
25
0
Order By: Relevance
“…These observations help validate the experimental approach and this ovary list. IGFBP2 is involved in growth inhibition in fetal development, and is abundant in Leydig cells (Wang et al 1994, Schneyer et al 2004, Terrien et al 2005, Yao 2005. AMH receptor 2 (AMHR2) is known to bind AMH to promote Mü llerian duct regression in the developing male, and to negatively regulate postnatal Leydig cell differentiation (Jamin et al 2002, Mendis-Handagama et al 2006.…”
Section: Discussionmentioning
confidence: 99%
“…These observations help validate the experimental approach and this ovary list. IGFBP2 is involved in growth inhibition in fetal development, and is abundant in Leydig cells (Wang et al 1994, Schneyer et al 2004, Terrien et al 2005, Yao 2005. AMH receptor 2 (AMHR2) is known to bind AMH to promote Mü llerian duct regression in the developing male, and to negatively regulate postnatal Leydig cell differentiation (Jamin et al 2002, Mendis-Handagama et al 2006.…”
Section: Discussionmentioning
confidence: 99%
“…Here, ECM-associated IGFBP-2 can act as a competitor for the IGF-I receptor (Pereira et al 2004), or the association of IGFBP-2 with the ECM itself may function as a cell targeting mechanism for IGFs. However, the findings that IGFBP-2 was also localized in the cytoplasm and on the nuclear surface (Hoeflich et al 2004) and interacts with the intracellular cell cycle inhibitor p21CIP1/WAF1 (Terrien et al 2005) show that IGFBP-2 exerts some of its actions directly within the cell. IGFBP-2 appears to have varying effects on different cell lines.…”
Section: Igfbp-2 Induction Of Genes Related To Apoptosismentioning
confidence: 99%
“…As a second pathway, IGFBP-2 has also been shown to bind to glycosaminoglycans, heparin, and proteoglycans (Arai et al 1996, Russo et al 1997, Conover & Khosla 2003, amongst others, by means of its heparinbinding domain (Russo et al 2005). In addition, IGFBP-2 was found to be localized on the cell surface (Pereira et al 2004, Russo et al 2005, in the cytoplasm, on the nuclear surface (Hoeflich et al 2004) and even within the nucleus (Terrien et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…IGF binding to its binding protein protects the IGF from proteolytic degradation resulting in increased bioavailability of circulating IGFs. In addition to their role in regulating the bioavailability of circulating IGF, it has become clear that IGFBPs can also exert effects on numerous cell functions, including proliferation, survival, gene transcription and the initiation of apoptosis [33][34][35][36](see review Baxter, R 2014) [37].…”
Section: Insulin-like Growth Factor (Igf) Axismentioning
confidence: 99%
“…We have shown that IGFBP-2 could promote prostate tumour progression by acting as a growth promoter and as a survival factor against docetaxel-induced cell death [134]. It has also been shown that IGFBP-2 plays an important role in promoting the metastatic ability of many cells including human dermal fibroblasts, breast cancer and glioma cells [33][34][35] through the interaction with -1 integrin receptors via the RGD sequence of IGFBP-2 [135]. This interaction leads to inactivation of phosphatase and tensin homolog (PTEN), a tumour suppressor gene and the phosphatase that normally restrains the PI3K/Akt pathway [136].…”
Section: The Role Of Igf System In Mediating Emtmentioning
confidence: 99%